Modeling, design and experiment of a remote-center-of-motion parallel manipulator for needle insertion. (April 2018) - Zhang, Ningbin; Huang, Pengcheng; Li, Qinchuan
Highlights: A novel remote-center-of-motion parallel manipulator for needle insertion is proposed. This dimension-optimized mechanism has singularity-free workspace with good motion/force transmissibility. Fixed linear actuators are adopted in parallel architecture, which inherently provides high rigidity. A prototype is built to validate the mobility and design. Abstract: In surgical procedures such as brachytherapy, biopsies and drainages, how to precisely place the needle inside the body is crucial for the performance of such surgeries. In last two decades, robot-aided needle placement has gradually been a trend for better security and accuracy. However, existing successful medical robot systems leave some common drawbacks: expensive, bulky, and high operation complexity, which motivates the development of more compact, affordable, and functional robots. This paper introduces a novel robot based on a 2-CRRR-CRR parallel manipulator (PM) for single needle insertion with high accuracy, where C denotes a cylindrical joint and R a revolute joint. Via screw theory, the mobility of the robot is analyzed, which meets the requirement of remote-center-of-motion (RCM). Its kinematic analysis is presented and singular configurations are identified based on the Jacobian matrix. Furthermore, the link dimensions of the robot are optimized by considering motion/force transmissibility and practical limits to generate singularity-free and high-performance workspace around the incision point. The design and feasibility of the proposed robot are validated by preliminary motion experiments with a prototype. The two advantages of the proposed robot are a singularity-free workspace with good motion/force transmissibility and high rigidity due to three fixed linear actuators in parallel architecture.